Numerical solutions to nonlinear Schrödinger equations in silicon waveguides (Journal of Humanitarian and Applied Sciences, 2023)
This research shows the most important properties of electromagnetic waves and waveguides as a means to transferring information, communications and various applications, and the importance of nonlinear equations and there solutions which represent Solitons or unilateral waves, and how to get solutions of the nonlinear Schrodinger equation where it will describe its optical picoseconds pulse spread in silicon waveguides, and the importance of silicon semi-conductor crystal and their features that enable them to interact with efficient nonlinear optical waves in the relatively low levels of electricity and distress. This paper shows the use of numerical solutions to nonlinear Schrödinger equations with finite difference method to solve, and graph the illustrations and comparisons to this topic using the experimental results of previous studies, to estimate various parameters needed for these solutions.
Keywords: Numerical solutions; nonlinear Schrödinger; equations